Enfermedades de filiación cultural en comunidades afro-mexicanas de la Costa Chica oaxaqueña y guerrerense - Luz María Espinosa Cortés; Alberto Ysunza Ogazón (AM. Rivista della Società Italiana di Antropologia Medica, 2010)
The cultural genesis of illness in Afro-Mexican communities of the Costa Chica oaxaqueña y guerrerense It has not been easy to identify the African roots of the health disease social representations among the Afro-Mexican population in the “Costa Chica” region, in the South Pacific Mexican coast. In contrast, there are regions such as the Caribbean and other Latino-American countries where the Yoruba medical practices have been reproduced and reinvented as well. Aguirre Beltran, an eminent Mexican medical anthropologist identifies as African cultural elements within the Traditional Medicine, two basic traditional diseases: “mal del animal” (animal sickness) and “la sombra” (the shadow). The present paper includes both of the mentioned syndromes and other with variations in their own explanation. Direct interviews were realized in a group of Afro-Mexican women and men are responsible for the welfare of their families. Women are usually those who first diagnose a sick member of the family; as well as those who make reference to the different cultural syndromes, which are cured by the local traditional medicine. Some of these syndromes had been identified by other ethnic groups as a evidence of the existing cultural parallelism. Enfermedades de filiación cultural en comunidades afro-mexicanas de la Costa Chica oaxaqueña y guerrerenseNo es fácil identificar las raíces africanas en la representación social del proceso saludenfermedad entre la población afro-mexicana de la región de la Costa Chica, en la costa del Pacífico sur de México, contrario a lo que ocurre en las zonas del Caribe y otros países de América latina, donde el “Medicina tradicional Yoruba” se ha reproducido y reiventado. El médico y antropólogo mexicano Aguirre Beltrán identificó dos elementos culturales africanos en la medicina tradicional: “el mal del animal” y “la sombra”. El presente trabajo incluye los síndromes mencionados y otros a partir de la explicación de un grupo de mujeres y hombres. Las mujeres por lo general son las primeras en diagnosticar si algún miembro de la familia se encuentra enfermo, así como identificar los síndromes culturales que lo afectan y que cura la medicina tradicional local. Algunos de los síndromes han sido identificados por otros grupos étnicos, por lo que estamos ante un paralelismo cultural.